# How do you find the intercepts for #y= -3x+6#?

By signing up, you agree to our Terms of Service and Privacy Policy

To find the intercepts for the equation ( y = -3x + 6 ), you set ( x ) or ( y ) to zero and solve for the other variable.

For the ( x )-intercept, ( y ) is set to zero: [ 0 = -3x + 6 ] [ 3x = 6 ] [ x = 2 ]

So the ( x )-intercept is ( (2, 0) ).

For the ( y )-intercept, ( x ) is set to zero: [ y = -3(0) + 6 ] [ y = 6 ]

So the ( y )-intercept is ( (0, 6) ).

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7